Elderly rats fed with a high-fat high-sucrose diet developed sex-dependent metabolic syndrome regardless of long-term metformin and liraglutide treatment - Ivić, Vedrana; Zjalić, Milorad; Blažetić, Senka; Fenrich, Matija; Labak, Irena; Scitovski, Rudolf; Szűcs, Kálmán Ferenc; Ducza, Eszter; Tábi, Tamás; Bagamery, Fruzsina; Szökő, Éva; Vuković, Rosemary; et al. (Frontiers in Endocrinology, 2023)
Aim/Introduction The study aimed to determine the effectiveness of early antidiabetic therapy in reversing metabolic changes caused by high-fat and high-sucrose diet (HFHSD) in both sexes. Methods Elderly Sprague–Dawley rats, 45 weeks old, were randomized into four groups: a control group fed on the standard diet (STD), one group fed the HFHSD, and two groups fed the HFHSD along with long-term treatment of either metformin (HFHSD+M) or liraglutide (HFHSD+L). Antidiabetic treatment started 5 weeks after the introduction of the diet and lasted 13 weeks until the animals were 64 weeks old. Results Unexpectedly, HFHSD-fed animals did not gain weight but underwent significant metabolic changes. Both antidiabetic treatments produced sex-specific effects, but neither prevented the onset of prediabetes nor diabetes. Conclusion Liraglutide vested benefits to liver and skeletal muscle tissue in males but induced signs of insulin resistance in females.